2004
DOI: 10.1111/j.1468-0440.2004.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Population Ageing and Health Care Expenditure: New Evidence on the “Red Herring”

Abstract: The observation that average health care expenditure rises with age generally leads experts and laymen alike to conclude that population ageing is the main driver of health care costs. In recently published studies we challenged this view (Zweifel et al., 1999;Felder et al., 2000). Analysing health care expenditure of deceased persons, we showed that age is insignificant if proximity to death is controlled for. Thus, we argued that population ageing per se will not have a significant impact on future health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 23 publications
11
102
0
9
Order By: Relevance
“…Zweifel et al reported cost of treatment to be an important driver of total cost, 19 similar to our study's findings. Patients receiving treatment with HCT experienced significantly higher cost when compared to those treated only with chemotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…Zweifel et al reported cost of treatment to be an important driver of total cost, 19 similar to our study's findings. Patients receiving treatment with HCT experienced significantly higher cost when compared to those treated only with chemotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…However, the generally negative impact of income on expenditure does not imply that insurance coverage should not be targeted at the poorest groups in the population; on the contrary, it suggests that policymakers need to ensure that these individuals are covered as they are less likely to purchase private insurance and are also more likely to be in poorer health. The recent Federal bill aimed at 51 Zweifel et al (1999Zweifel et al ( , 2004 …”
Section: Discussionmentioning
confidence: 99%
“…40 Future research could use the disability-adjusted LE data to more accurately estimate 36 Fries (2000). 37 See, for example, Newhouse (1977); Gerdtham et al (1992); Hitiris and Posnett (1992); Zweifel et al (2004). 38 Chou (2007).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%